PENERAPAN MODEL PEMBELAJARAN PEMECAHAN MASALAH (PROBLEM SOLVING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 117 PEKANBARU - Fitri Yani; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on preliminary data obtained by researchers showed that the achievement of learning outcomes largely Elementary School fifth grade students 117 Pekanbaru is still relatively low, the number of students 36 people composed of 19 men and 17 women. KKM specified is 75. The number of students who reach KKM only 15 and who have not reached KKM completeness 21 people with a percentage of 41,66% and an average grade 68.47. This is due to more students are positioned as an object, the student is considered not to know and not know anything, while positioning himself as a teacher who has knowledge. So that the learning has focused on teacher (teacher center) while students more silent and hear the teacher explained. Only a few students who are active in the learning process. Therefore, the goal of researchers to improve the results of students' mathematics learning through problem-solving learning model in the Elementary School fifth grade students in the academic year 2014/2015 117 Pekanbaru. This research method is Action Research (PTK) carried out by 2 cycles with 4 meetings and 2 replications. Research subjects fifth grade students of SD Negeri 117 Pekanbaru the number of students 36 people. From the research results mean learning outcomes 75.27 mathematics in the first cycle, the second cycle 82.77. Mastery learning students in the first cycle and cycle II 61.11% 83.33%. The activities of teachers in the first cycle of 80% with the good category and the second cycle of 92.5% with very good category. Activity of students in the first cycle of 67.5% with the good category and the second cycle of 87.5% with very good category. It can be concluded that the application of learning models problem solving (problem solving) can improve the results of learning mathematics Elementary School fifth grade students 117 Pekanbaru.Keywords : Problem Solving Learning Model (Problem Solving), Mathematics Learning Outcomes.